University Students' Achievement of Meaningful Learning through Participation in Thinking Routines - Nora Ramos-Vallecillo; Víctor Murillo-Ligorred; Raquel Lozano-Blasco (MDPI AG, 2024)
This study was conducted among undergraduate students pursuing a Primary Education degree at the University of Zaragoza. Its primary aim was to enhance and elevate the quality of participation during theoretical sessions, thereby fostering meaningful learning that contributes to the improvement of academic performance among the participants. To achieve this objective, a quasi-experimental case study was meticulously crafted. This research design was structured to not only stimulate and augment participation but also to cultivate meaningful learning, ultimately enhancing students' academic achievements. The study employed a comprehensive approach to monitor participation, utilizing observation records to track engagement levels, and anecdotal records to delineate the progression of sessions and the quality of responses. Through meticulous analysis, it can be deduced that the integration of thinking routines as a pedagogical tool in expository sessions significantly enhances student engagement. These routines effectively activate students' prior knowledge, establishing meaningful connections with the subject matter at hand. Moreover, the incorporation of thinking routines has been observed to elevate the quality of student participation. By fostering reflective practices, aiding in the formulation of inquiries, promoting collaborative learning, and nurturing critical thinking skills, these routines play a pivotal role in enriching the educational experience and bolstering academic performance.